A Spanish-language translation for the U.S. of the type 2 diabetes stigma assessment scale (DSAS-2 Spa-US) - Joiner, Kevin L.; Adams, Mackenzie P.; Bayrakdar, Amani; Speight, Jane (Frontiers in Clinical Diabetes and Healthcare, 2022)
Background Diabetes stigma is recognized to negatively impact health-related outcomes for people living with type 2 diabetes (T2D), but there is a dearth of evidence among U.S. Latino adults with T2D. Our aim was to develop a Spanish-language translation of the Type 2 Diabetes Stigma Assessment Scale (DSAS-2) and examine its psychometric properties among U.S. Latino adults with T2D. Methods The translation was developed through a multi-step process, including a focus group with community health workers (n=5) and cognitive debriefing interviews with Latino adults with T2D (n=8). It was field-tested in an online survey of U.S. Latino adults with T2D, recruited via Facebook (October 2018 to June 2019). Exploratory factor analysis examined structural validity. Convergent and divergent validity were assessed by testing hypothesized correlations with measures of general chronic illness stigma, diabetes distress, depressive and anxiety symptoms, loneliness, and self-esteem. Results Among 817 U.S. Latino adults with T2D who participated in the online survey, 517 completed the Spanish-language DSAS-2 (DSAS Spa-US) and were eligible for the study (mean age 54 ± 10 years, and 72% female). Exploratory factor analysis supported a single-factor solution (eigenvalue=8.20), accounting for 82% of shared variance among the 19 items, all loading ≥ 0.5. Internal consistency reliability was high (α=0.93). As expected, strong, positive correlations were observed between diabetes stigma and general chronic illness stigma (rs=0.65) and diabetes distress (rs=0.57); medium, positive correlations, between diabetes stigma and depressive (rs=0.45) and anxiety (rs=0.43) symptoms, and loneliness (rs=0.41); and a moderate negative correlation between diabetes stigma and self-esteem (rs=-0.50). There was no relationship between diabetes stigma and diabetes duration (rs=0.07, ns). Conclusion The DSAS-2 Spa-US is a version of the DSAS-2, translated into Spanish, that has good psychometric properties for assessing diabetes stigma in U.S. Latino adults with T2D.